Africa RISING Ethiopia RHoMIS 2018 - International Livestock Research Institute (International Food Policy Research Institute, 2020)
This dataset is a result of a household survey of farmers who engaged with the Africa RISING Ethiopia program, for a period of about 4 years. The purpose was to assess the degree of uptake of Africa RISING promoted interventions (farm-integration, sustainable intensification); and to evaluate possible impacts of uptake on various indicators of ?sustainability?. The outcome indicators related to agricultural production, human welfare, gender roles, innovation, food security, and poverty.